The Assessment Purpose Triangle: Balancing the Purposes of Educational Assessment - Archer, Elizabeth (Frontiers in Education, 2017)
This article introduces the concept of the Assessment Purposes Triangle in order to illustrate the balancing of purposes that needs to be considered in assessment for educational quality. The triangle is a visual aid for stakeholders making value judgements about equitable resource allocation in an environment of scarcity. The article argues that each of the three basic purposes of assessment, Assessment to support learning; Assessment for accountability; Assessment for certification, progress and transfer need to enjoy appropriate attention to support quality education. Accountability and certification, progress and transfer are inherently high stakes due to systemic pressures such as institutional funding, accreditation with various bodies, legislative requirements, national and international competition, and public and media pressure. It is thus likely that resources will be diverted to these purposes from the lower stakes Assessment to support learning. The article illustrates the inherent dangers of over-emphasising certain purposes to the detriment of others in any educational system. It also discusses the power inherent in assessment and argues for a harnessing of this power for quality education through catering for the three basic assessment purposes in an equitable manner. All actors in an educational system should be cognizant of the goals of the education system as a whole when developing and engaging with assessment. The article provides a conceptual tool for stakeholders in educational assessment to engage with these goals when considering the allocation of appropriate resources to each of the assessment purposes.